Analysis of Factors Influencing Farmers’ Decisions in Using Certified Seeds in Pemayung District Batang Hari Regency - Dina Yuliasty Lamefa; Reno Armando; Enita; Uliya; Dian Purnomo (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
This study was conducted with the objectives: 1). To identify factors that influence farmers' decisions in using certified seeds in Pemayung District. 2). To analyze factors that influence farmers' decisions in using certified seeds in Pemayung District. The study was carried out in the Batang Hari Regency's Pemayung District. Because the majority of rice growers here utilize certified seeds, this location was selected. After the discussion, a constant value (a) of -3.085 was determined. This indicates that the value of the seed usage decision is -3.085 if all the factors under study (age, income, experience, education level, and land area) have values equal to zero (0). The value of the age coefficient (b1) is 0.142. This indicates that, provided the values of the other variables remain constant, an increase of one unit in the age variable will result in a 0.142 unit drop in the seed usage decision's value. The coefficient value (b2) for education level is 0.518. The results of Nagelkerke R Square demonstrate the influence of the variables of age (X1), education (X2), farming experience (X3), land area (X4), and income (X5) on this variable. This indicates that a 42% explanation of the dependent variables can be attributed to the independent variables in the model. Other factors not included in this study, such as the activity of farmer groups, risk preferences, land ownership status, and others, account for the remaining 58% (100% - 58%). The Education variable, with a Wald value of 4.613 and a Significance value of 0.032, and the Business Experience variable are the variables with a Wald value larger than 3.841 and a significance level lower than 0.05. While other factors, such as income, land area, and age, have significance values larger than 0.050 and Wald values smaller than 3.841, they have no effect on farmers' decisions to use certified seeds.